The Influence of Prenatal Yoga Exercise on Mother Anxiety Pregnant at PMB Mamah Suhaeriah in 2022 - Suhaeriah, Mamah; Telaumbanua, Linda K; Sianipar, Astrid F; Nurmah, Nurmah (NHM PRESS, 2022)
Anxiety during pregnancy not only affects the health of pregnant women but can also have an impact on the delivery process such as premature labor, prolonged labour, cesarean delivery, low birth weight. Based on WHO data, there are around 10% of pregnant women with psychological disorders and about 13% of postpartum women worldwide. This incidence is higher in developing countries in pregnant women, namely 15.6% and 19.8% in postpartum women. The purpose of this study is The Effect of Prenatal Yoga Exercise on the Anxiety of Pregnant Women at TPMB Mamah Suhaeriah in 2022. Research method This type of research uses the Pre-Experimental method with a one group pretest-posttest design approach. Sampling using total sampling with a total sample of 20 respondents. The research instrument used was an observation sheet. The data analysis used is the Wilcoxon Sign Rank Test statistical test. Research results based on the results of statistical tests using the Wilcoxon Sign Rank test, the p-value (0.000 <0.05) is obtained. This states that Ha is accepted. Conclusion there is an effect of prenatal yoga exercise on the anxiety level of pregnant women at TPMB Mamah Suhaeriah in 2022. The advice for pregnant women is to be able to manage their psychological state well, and do exercise regularly, because exercise has good benefits for survival during pregnancy.